Strategi Pendidikan Agama Islam dengan Metode Thing Pair Share pada Tingkat Madrasah - Zulihi1, Zulihi; Umkabu, Talabudin (JOEAI (Journal of Education and Instruction), 2023)
This study was done to determine the role of the object pair and share cooperative learning approach at the madrasah level in presenting Islam education, which up to this point has only used the traditional system. This study was also done to determine how engaged the student or students were in using this form of learning. especially on content about Islam. The classroom action research approach, which was derived from Kemmis & Tagart's approach, was employed in this study. This approach is a two-cycle research paradigm that includes several steps, including planning, action implementation, observation, and method reflection. This study's major goal is to find out how much is known about the cooperative think pair and share (TPS) approach used to offer Islamic religious instruction. According to the study's findings, there has been an upsurge in Madrasah-level Islamic religious education activities. In conclusion, the Think, Pair, and Share approach is a technique that helps boost students' creativity, which can make them more engaged in discussions, receptive to other people's viewpoints, and active in both teaching and learning. Keywords: Madrasah, Islamic Religious Education, Think Pair Share